PROBLEMATIKA PEMBELAJARAN DARING SISWA KELAS VII SMPN 1 ENDE SELATAN, KABUPATEN ENDE - Maria Kristina Ota; Ana Maria Gadi Djou; Filzah Farid Numba (LPPM Universitas Flores, 2021)
The pandemic of covid 19 had big effects in educational field. The transition of learning process from face to face into online had many obstacles. Teachers, students and parents had their own problems to face it. Parents had to provide facilities to their child during online learning process but their economic factors were inadequate, such as buying android phone or data package. There were parents and teachers were not able to use the technology effectively and efficiently. It can be effect to the students. Students will left behind the materials and the assignments had given by their teachers. Door to door was an approach offered to avoid or to minimize that problems. The aim of that approach was teachers could share the materials, the assignment and guiding their students directly. Learning guidance could be the materials which were not understood and teaching them how to use android phone to access the materials shared through online learning. In order that, door to door approach which had implemented besides helped students to understand more the materials but also the students got learning guidance effectively about the way to utilize the learning technology. It was about the materials were shared online. In this case, teacher should actively guiding their students to use the technology in better way. Furthermore, the teacher will adding new knowledge, so they do not seems out of touch of information and blinded technology.